PENGEMBANGAN SISTEM AUDIT TERINTEGRASI PADA SIAKAD MENGGUNAKAN FRAMEWORK COBIT 5 - Kurniawan, Andri; Situmeang, Nur Ansori Hamidah; Falgenti, Kursehi (INTI Nusa Mandiri, 2025)
The Academic Information System (SIAKAD) plays a crucial role in supporting academic activities within the university environment. Evaluating the system's maturity is necessary to identify weaknesses and potential improvements. Therefore, periodic audits of SIAKAD are essential to obtain constructive feedback from stakeholders. Conducting regular audits of SIAKAD is more effective when supported by an application integrated with the system. This study aims to develop an audit system integrated with SIAKAD. The COBIT 5 framework is used for auditing SIAKAD, while the audit system is developed using PHP programming language and a MySQL database. The focus of this research is the development of an audit system within the Evaluate, Direct, and Monitor (EDM) domain. This study proposes a new approach to developing an effective SIAKAD audit system by integrating SIAKAD with a COBIT 5-based audit system. The developed audit system has been tested on a limited scale with 20 respondents from the Bantaeng Manufacturing Industry Community Academy. At this stage, the audit system development has only reached the process of summarizing questionnaire results. The calculation of SIAKAD maturity levels has not yet been integrated and is still performed manually. Gap analysis results indicate that SIAKAD’s maturity level remains low, with the following scores:EDM1: 30, EDM2: 20, EDM3: 33.6, EDM4: 16.7, and EDM5: 23.3. Based on these maturity scores, improvements in governance are required, particularly in the EDM2 and EDM4 subdomains.